WIMP physics with ensembles of direct-detection experiments - Peter, Annika H.G.; Glusevic, Vera; Green, Anne M.; Kavanagh, Bradley J.; Lee, Samuel L. (Elsevier, 2014)
The search for weakly-interacting massive particle (WIMP) dark matter is multi-pronged. Ulti- mately, the WIMP-dark-matter picture will only be confirmed if different classes of experiments see consistent signals and infer the same WIMP properties. In this work, we review the ideas, meth- ods, and status of direct-detection searches. We focus in particular on extracting WIMP physics (WIMP interactions and phase-space distribution) from direct-detection data in the early discov- ery days when multiple experiments see of order dozens to hundreds of events. To demonstrate the essential complementarity of different direct-detection experiments in this context, we create mock data intended to represent the data from the near-future Generation 2 experiments. We consider both conventional supersymmetry-inspired benchmark points (with spin-independent and -dependent elastic cross sections just below current limits), as well as benchmark points for other classes of models (inelastic and effective-operator paradigms). We also investigate the effect on parameter estimation of loosening or dropping the assumptions about the local WIMP phase-space distribution. We arrive at two main conclusions. Firstly, teasing out WIMP physics with experi- ments depends critically on having a wide set of detector target materials, spanning a large range of target nuclear masses and spin-dependent sensitivity. It is also highly desirable to obtain data from low-threshold experiments. Secondly, a general reconstruction of the local WIMP velocity distribu- tion, which will only be achieved if there are multiple experiments using different target materials, is critical to obtaining a robust and unbiased estimate of the WIMP mass.